(3OjhGf GdGOHs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3Chdg fGbU hChd GdehLhO efg(B: (3HGH GdeaGYdg hgh eeG RjOJ Hjf CdaG efg hGdYjf Cda bGd cYH Hf eGdc GdfUGQi RYeJ SNjfI Cf jSJZdH s
(3BNQgG (B:s
(3BNQg fGbU hBNQ GdehLhO efg (B: (3HGH GdaYddg HeYfi HGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B774s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs